Fixação de nitrogênio (redução de acetileno) em cupins (Insecta: Isoptera) da Amazônia Central - Sylvester-bradley, Rosemary; Bandeira, Adelmar Gomes; Oliveira, Luiz Antonio de (Acta Amazonica, 1978)
Twenty one species of termites were collected from their nests in areas of pasture, secondary forest and primary forest at a cattle ranch in Central Amazonia, Brazil. Theyi were tested immediately for nitrogenase (acetylene reducing) activity. The highest activities (more than 100 nmoles C2H4 produced/g dry weight/hour) all occurred in termites of the genus Nasutitermes collected in the pasture. Nasutitermes is known to be the commonest genus in the area. The rates of acetylene reduction detected in termites from primary and secondary forest were lower than in the pasture; Nasutitermes was not tested in the secondary forest however. The difference in rate of acetylene reduction between workers and soldiers wall small. Rates were linear within three hour incubation periods except in two out of nine cases. Nitrogen fixation associated with termites may be an important ecological factor in Central Amazonia.